ANALISIS KEPUASAN KONSUMEN TERHADAP PELAYANAN PENJUAL KERBAU DI PASAR HEWAN BOLU KECAMATAN TALLUNGLIPU KABUPATEN TORAJA UTARA - Suprianto Suprianto; Astati Astati (Jurnal Ilmu dan Industri Peternakan, 2016)
Sponge animal market is located in the tourist center of Toraja, Rantepao City, Bolu market already well known as an attractive tourist destination and a unique place to visit. Cattle market, so the market is also known, is a sales center buffalo. Sponge animal market as marketing services should attach great importance to customer services, it dikarena sponge animal market is the only market that is the largest animal ditana Toraja. The buyer need to buy livestock covering the needs of the funeral, to be kept back, marriage ceremony and celebration for families who return from overseas. Services are less well able resulted in revenue would be reduced because consumers will seek out livestock animal markets sponge due to inferior services to consumers / communities. Therefore, there will be a study entitled "Analysis of Consumer Satisfaction Of Service Sellers Buffalo Animals In The Market Bolu Tallunglipu District of North Toraja Regency". The purpose of this study was to determine the level of customer satisfaction with service seller buffaloes (reliability, responsiveness, assurance, empathy, tangible) In Bolu Animal Market district. Tallunglipu Kab. North Toraja.   This study began in March until april 2015 is housed in the District Tallunglipu , North Toraja regency . This type of research is descriptive quantitative research . The population in this study is not limited sample of 100 farmers . Data used in this study is qualitative and quantitative data . The data used in this study are primary and secondary data . The data collection method used in this study is the observation and interviews . The type of data analysis used in this study are Importance Performance Analysis ( IPA ) .The results showed that the average level of concordance indicator measuring consumer satisfaction in the ministry, buffalo cattle dealer that is 87.3 % . This indicates that the expectations of consumers regarding the quality of services provided by the seller of cattle remains below reality accepted by consumers so that it can be said that consumers are still not satisfied . Based on the mapping of the Cartesian quadrant of the diagram shows that the performance attributes should get top priority for improvement in order to meet the needs and desires of consumers in receiving the service seller buffaloes . The conclusion of this study is that consumers are not satisfied with the services the seller buffaloes